2021
DOI: 10.1371/journal.pmed.1003798
|View full text |Cite
|
Sign up to set email alerts
|

Testing approaches to sharing trial results with participants: The Show RESPECT cluster randomised, factorial, mixed methods trial

Abstract: Background Sharing trial results with participants is an ethical imperative but often does not happen. We tested an Enhanced Webpage versus a Basic Webpage, Mailed Printed Summary versus no Mailed Printed Summary, and Email List Invitation versus no Email List Invitation to see which approach resulted in the highest patient satisfaction with how the results were communicated. Methods and findings We carried out a cluster randomised, 2 by 2 by 2 factorial, nonblinded study within a trial, with semistructured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Although the emphasis for reporting to participants should be on information pertinent to their comparison, many participants will wish to hear about all aspects of the protocol; participants may talk together and it is fairer to transparently offer results from across the protocol’s activities to all participants should they want it [ 27 ]. Communicating efficacy results and emerging safety data requires careful tailoring to participants who were in the comparison, participants whose future management in the trial may be impacted by the findings, and participants elsewhere in the platform.…”
Section: Results—findings and Recommendationsmentioning
confidence: 99%
“…Although the emphasis for reporting to participants should be on information pertinent to their comparison, many participants will wish to hear about all aspects of the protocol; participants may talk together and it is fairer to transparently offer results from across the protocol’s activities to all participants should they want it [ 27 ]. Communicating efficacy results and emerging safety data requires careful tailoring to participants who were in the comparison, participants whose future management in the trial may be impacted by the findings, and participants elsewhere in the platform.…”
Section: Results—findings and Recommendationsmentioning
confidence: 99%
“…Most discussions about sharing research findings state that participants would like to know about the findings. 12,15,41 However, it is also acknowledged that in practice research findings are not shared as often as they should be. 15,22,41 Indeed, whilst health researchers agree on the importance of making research publicly accessible, it is often admitted that it is 'easy to become untethered from these foundational principles'.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,41 However, it is also acknowledged that in practice research findings are not shared as often as they should be. 15,22,41 Indeed, whilst health researchers agree on the importance of making research publicly accessible, it is often admitted that it is 'easy to become untethered from these foundational principles'. 42 The failure to share research findings with participants has been shown to impact researcher credibility and an individual's future participation in research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the emphasis for reporting to participants should be on information pertinent to their comparison, many participants will wish to hear about all aspects of the protocol; participants may talk together and it is fairer to transparently offer results from across the protocol's activities to all participants should they want it. 20 Communicating e cacy results and emerging safety data requires careful tailoring to participants who were in the comparison, participants whose future management in the trial may be impacted by the ndings and participants elsewhere in the platform. Ideally, participants would ag whether they wanted ndings from only "their" comparisons, results from other comparisons, or no results.…”
Section: Reportingmentioning
confidence: 99%